Uncovering the core principles of the gut-lung axis to enhance innate immunity in the chicken - Saint-Martin, Vincent; Quéré, Pascale; Trapp, Sascha; Guabiraba, Rodrigo (Frontiers in Immunology, 2022)
Research in mammals has evidenced that proper colonization of the gut by a complex commensal microbial community, the gut microbiota (GM), is critical for animal health and wellbeing. It greatly contributes to the control of infectious processes through competition in the microbial environment while supporting proper immune system development and modulating defence mechanisms at distant organ sites such as the lung: a concept named 'gut-lung axis'. While recent studies point to a role of the GM in boosting immunity and pathogen resilience also in poultry, the mechanisms underlying this role are largely unknown. In spite of this knowledge gap, GM modulation approaches are today considered as one of the most promising strategies to improve animal health and welfare in commercial poultry production, while coping with the societal demand for responsible, sustainable and profitable farming systems. The majority of pathogens causing economically important infectious diseases in poultry are targeting the respiratory and/or gastrointestinal tract. Therefore, a better understanding of the role of the GM in the development and function of the mucosal immune system is crucial for implementing measures to promote animal robustness in commercial poultry production. The importance of early gut colonization in the chicken has been overlooked or neglected in industrial poultry production systems, where chicks are hampered from acquiring a complex GM from the hen. Here we discuss the concept of strengthening mucosal immunity in the chicken through GM modulation approaches favouring immune system development and functioning along the gut-lung axis, which could be put into practice through improved farming systems, early-life GM transfer, feeding strategies and pre-/probiotics. We also provide original data from experiments with germ-free and conventional chickens demonstrating that the gut-lung axis appears to be functional in chickens. These key principles of mucosal immunity are likely to be relevant for a variety of avian diseases and are thus of far-reaching importance for the poultry sector worldwide.